2019
DOI: 10.1186/s12920-019-0542-3
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative analysis of loss-of-function variants in clinical and genomic data reveals novel genes associated with cardiovascular traits

Abstract: Background Genetic loss-of-function variants (LoFs) associated with disease traits are increasingly recognized as critical evidence for the selection of therapeutic targets. We integrated the analysis of genetic and clinical data from 10,511 individuals in the Mount Sinai Bio Me Biobank to identify genes with loss-of-function variants (LoFs) significantly associated with cardiovascular disease (CVD) traits, and used RNA-sequence data of seven metabolic and vascular tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Following Kuang et al ( 2020 ), we counted the total number of missense and loss‐of‐function (LoF) homozygous derived sites, and divided those numbers by the total count of synonymous sites. To define LoF sites, we chose the approach of Glicksberg et al ( 2019 ), and considered only sites of high impact under the effect categories “stop_gained,” “frameshift_variant,” “splice_acceptor_variant” and “splice_donor_variant.”…”
Section: Methodsmentioning
confidence: 99%
“…Following Kuang et al ( 2020 ), we counted the total number of missense and loss‐of‐function (LoF) homozygous derived sites, and divided those numbers by the total count of synonymous sites. To define LoF sites, we chose the approach of Glicksberg et al ( 2019 ), and considered only sites of high impact under the effect categories “stop_gained,” “frameshift_variant,” “splice_acceptor_variant” and “splice_donor_variant.”…”
Section: Methodsmentioning
confidence: 99%
“…We expect that further studies in larger sample sizes and multi-center Thai male and female populations will help to confirm the feasibility of using the FH-CHD biomarker in Thai ethnicities. Moreover, further meta-analysis studies using publicly available transcriptomic data from different ethnic populations to compare and share appropriate CHD biomarker is expected to be more reliable and advantageous; (5) Several current studies into the genetic basis of coronary heart disease have intensively reported the discovery and aggregation of genetic variants from multiple genes from lipid and other pathologic pathways ( Yao et al, 2015 ; Glicksberg et al, 2019 ; Cohain et al, 2021 ). Based on our current NGS data, we are continuing to investigate the variant genes observed only in FH and FH-CHD patient groups, to identify potential predictive markers.…”
Section: Resultsmentioning
confidence: 99%
“…With approximately 10 million independent variants generated using WGS, reaching a genome-wide threshold is very unlikely to identify variants associated with a rare allele frequency, low relative risk, and low fraction of variance explained, even if they are the causal variants 38 . Therefore, using lenient p-value thresholds (p < 0.1 for discovery) 39 , we focused on LOF variants with a high-penetrance conferring moderate or high risk, even if those were common allelic frequency, showing evidence for pathway-related co-expression in human cerebral tissue. Second, there might have been a potential bias related to the physician's independent choice of antidepressant drug because of the study's naturalistic design of the study.…”
Section: Discussionmentioning
confidence: 99%